The Strategy of Developing Patients’ Safety Culture in Hospital - Hilda Hilda; Arsyawina Arsyawina; Edi Sukamto; Rahmat Bakhtiar; Supriadi Supriadi; Rivan Firdaus; Emmy Putri W. (Humanistic Network for Science and Technology (HNST), 2021)
The important factor affecting patients’ treatment and safety service quality is patients’ safety culture. This research aimed to identify the most effective strategy to develop the patients’ safety culture to prevent nursing error in the highest referral hospital in East Kalimantan Province. This research is a mix method. The population in this study were all nurses in the inpatient room totaling 342 people and a sample of 119 people obtained by proportional random sampling. In quantitative research, data were obtained using questionnaires and then analyzed using multiple linear regression. While qualitative data were obtained through in-depth interviews with 3 informants, namely the implementing nurse, the head of the inpatient room and the chairman of the patient safety committee. The results of the analysis show that there are two environmental factors that influence patient safety culture, namely lifesaving control (p value = 0.002) and patient safety (p value = 0.041). Through in-depth interviews, it is known that individual, organizational, and environmental factors are effective in developing a patient safety culture.Keywords: strategy; development; patients safety culture